Uma cartografia da leitura: o imaginário leitor fortalezense na segunda metade do século XIX - Braga, Felipe Alves de Lima (2018)
This research seeks to investigate the reading and the reader context of the city of Fortaleza in the second half of the nineteenth century, under the informational bias. It is intended, as an intention, to recover part of the historiography and local literature of this phase, trying to understand how the socio-cultural dynamics influenced the intellectual productions of this period and the readings made by the population. In order to do so, we investigated the literary associations that emerged in the city at that time, and attributed to them the first literary productions of Ceará. Understanding the city and its complexities as the motto of the plot of many of these literary works, we investigated how the intellectuals of these groups saw the city and retract their daily life, as well as seeking to identify the literary and reading influences of these subjects. In the search to draw a cartography reader of Fortaleza, the concepts of information, reading, imagery and memory are approached in order to understand the local historical context under the bias of information theories. In this sense, we tried to answer the problematic: How did the formation of the reader's imagination strengthen in the second half of the nineteenth century? From this perspective, the general objective of the study was to investigate the formation of the reader's imagination in the second half of the nineteenth century, focusing on institutions: the Provincial Library, the Ceará Institute and the Ceará Academy of Letters. The specific objectives were: a) to identify the information and production flows of knowledge of the city at that time; ; b) map the cultural milestones that contributed to the formation of the imaginary reader of the capital; c) to know the socio-cultural and historical panorama of Fortaleza at the end of the 19th century; and d) to understand the role of the three institutions chosen in the construction of the city and its daily reader in the aspects of assimilation, production and dissemination of information and knowledge. As a methodological strategy, the research is exploratory and descriptive, being a bibliographical and documentary research, with a qualitative approach, using the historical method. It is concluded that the reading panorama of the city of Fortaleza in the period was formed by a small information network made up of newspapers, book traders and book associations, as well as a historical context with strong influences of the European civilizational ideals, in the so-called Belle Époque. The imaginary reader of the time was based on a civilizational polítical project based on the philosophy of the lights and the scientific ideas imported from Europe. The intellectual elite embellished a cultured society and as that same elite circulated in the polítical and power spheres of the citizenry, they idealized a society that had as its greatest gear for the development of literate and erudite culture. The Provincial Library, the Ceará Institute and the Ceará Academy of Letters ratify this project by inaugurating a tradition of scientific and literary production in the city that sought to introduce progress through its productions, as well as to encourage the search for a local identity through the production of knowledge about the colonial history of the Province, about local geography and the positive impacts of the introduction of technologies for the socioeconomic progress of the state. Therefore, the imaginary of progress through the letters, influenced by the European scientific and civilizing postulates and the search for a local and national identity, form the basis of the imaginary of this period.